(untitled) (Research, Society and Development, 2022)
The objective was to evaluate the microbiological and physical-chemical quality, in addition to verifying the presence of antibiotic residues in refrigerated raw milk samples collected in four individual and five collective tanks located in rural properties belonging to the municipality of Alegre/ES. The samples were coded, placed in sterilized vials and transported to the Laboratory of Microbiology and Biotechnology of the Federal Institute of Espírito Santo Ifes, Campus de Alegre/ES. Microbiological analyzes were performed for total bacterial count and Staphylococcus aureus; physicochemical; in addition to the detection of residues of antibiotics from the β-lactam and tetracycline groups. The mean values for TBC were between 2.0 x 104 CFU mL-1 and 3.0 x 107 CFU mL-1 and it was found that 44.44% of the samples were in compliance with the legislation. The values of S. aureus were between <102 and 3.6x106 CFU mL-1 and these results are worrying due to the possibility of the formation of heat-resistant toxins, in addition to being a microorganism that causes mastitis. Regarding the physicochemical analyses, 33.33% were in compliance with the legislation and in all samples there were no antibiotic residues. It was concluded that only the samples collected in individual refrigeration tanks A6 and A7 were in accordance with current legislation. Changes are needed in the management practices adopted to obtain milk with quality and safety. The adoption of these measures would allow obtaining milk with quality and safety, in addition to contributing to the health of consumers and to the sustainability of the sector in the region and in the state of Espírito Santo.